2013
DOI: 10.1016/j.wasman.2013.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness of recycling: A systems model

Abstract: Financial analytical models of waste management systems have often found that recycling costs exceed direct benefits, and in order to economically justify recycling activities, externalities such as household expenses or environmental impacts must be invoked. Certain more empirically based studies have also found that recycling is more expensive than disposal. Other work, both through models and surveys, have found differently. Here we present an empirical systems model, largely drawn from a suburban Long Isla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 71 publications
1
12
0
2
Order By: Relevance
“…Environmental Proactivity (EP) EP1: Top management support/commitment and manpower involvement including environmental training Toke et al, 2012;Sambasivan et al, 2013;Jabbour et al, 2013 EP2: Approach to increase environmental expenditure (operational cost, training cost, environmentally friendly materials cost, waste and water treatment/recycling cost) Sambasivan et al, 2013;Sueyoshi and Goto, 2009;Wang et al, 2014 EP3: Approach to maintain regulations imposed by the government and stakeholders Cong and Freedman, 2011;Zhu et al, 2013; Lannelongue and Gonz alez-Benito, 2012 EP4: Approach to have ISO 14001 certification or environmental policy or formal environmental management system (EMS) for green manufacturing (GM) and green supply chain management (GSCM) Jabbour et al, 2013;Toke et al, 2012;Casadesús et al, 2008;Testa et al, 2014 EP5: Approach to have total quality management system/ISO 9001 certification Casadesús et al, 2008;Zhu et al, 2013;Terziovski et al, 2003 EP6: Long term sustainable initiative regarding GM and GSCM over budget schedule Toke et al, 2012;Sambasivan et al, 2013;Joung et al, 2012 EP7: Recycling initiatives like joining local recycling enterprises or establishing collaboration with same sector/industry Ricoh Group Sustainability Report , 2007, Toke et al, 2012Tonjes and Mallikarjun, 2013 EP8: Intelligent environmental management or communication management to exchange green initiatives among similar sectors Mandal and Sarkar, 2012;Burke and Gaughran, 2006;Butler, 2011 EP9: Life cycle assessment with environmental database of products Zhu and Deshmukh, 2003;Hon and Xu, 2007;Chung and Wee, 2011 EP10: Approach of green or eco-design (with cross-functional integration, if required) Jabbour et al, 2013;Tok...…”
Section: Related Variables Sourcesmentioning
confidence: 99%
“…Environmental Proactivity (EP) EP1: Top management support/commitment and manpower involvement including environmental training Toke et al, 2012;Sambasivan et al, 2013;Jabbour et al, 2013 EP2: Approach to increase environmental expenditure (operational cost, training cost, environmentally friendly materials cost, waste and water treatment/recycling cost) Sambasivan et al, 2013;Sueyoshi and Goto, 2009;Wang et al, 2014 EP3: Approach to maintain regulations imposed by the government and stakeholders Cong and Freedman, 2011;Zhu et al, 2013; Lannelongue and Gonz alez-Benito, 2012 EP4: Approach to have ISO 14001 certification or environmental policy or formal environmental management system (EMS) for green manufacturing (GM) and green supply chain management (GSCM) Jabbour et al, 2013;Toke et al, 2012;Casadesús et al, 2008;Testa et al, 2014 EP5: Approach to have total quality management system/ISO 9001 certification Casadesús et al, 2008;Zhu et al, 2013;Terziovski et al, 2003 EP6: Long term sustainable initiative regarding GM and GSCM over budget schedule Toke et al, 2012;Sambasivan et al, 2013;Joung et al, 2012 EP7: Recycling initiatives like joining local recycling enterprises or establishing collaboration with same sector/industry Ricoh Group Sustainability Report , 2007, Toke et al, 2012Tonjes and Mallikarjun, 2013 EP8: Intelligent environmental management or communication management to exchange green initiatives among similar sectors Mandal and Sarkar, 2012;Burke and Gaughran, 2006;Butler, 2011 EP9: Life cycle assessment with environmental database of products Zhu and Deshmukh, 2003;Hon and Xu, 2007;Chung and Wee, 2011 EP10: Approach of green or eco-design (with cross-functional integration, if required) Jabbour et al, 2013;Tok...…”
Section: Related Variables Sourcesmentioning
confidence: 99%
“…Although recycling is itself an energy consuming process and can cause extra greenhouse gases emission, emission of atmospheric pollutants from recycling materials would be much lower than emission of the same pollutants from raw materials (Bohm et al 2010, pp. 864 -871;Tonjes & Mallikarjun 2013, p. 2548. For example, recycling of paper causes 75% reduction of air pollution, 50% energy saving and 90% reduction of water pollution compared with production of paper from wood and raw materials (Craighill & Powell 1996, pp.…”
Section: Option 3: Recyclingmentioning
confidence: 99%
“…Tonjes & Mallikarjun (2013) who carried out cost effectiveness analysis of seven different scenarios of refuse a collection in New York. Other studies investigated the costs of different collection schemes of waste such as Beigl & Salhofer (2004), Groot et al (2014) and Larsen et al (2010); they compared all relevant costs of the different options in collection and concluded the difference in cost between the methods is relatively small.…”
Section: Developing the Quality Cost Approachmentioning
confidence: 99%
“…The study found that the net economic sustainability of the recycling of packaging waste is largely dependent on the type of packaging material recycled. Similar to Tonjes & Mallikarjun (2013), the study considers the collection costs at supplier as the cost of recycling. Consequently, the recycle cost at supplier is estimated as a sum of direct and indirect costs of collection process.…”
Section: Developing the Quality Cost Approachmentioning
confidence: 99%